2021
DOI: 10.3892/ol.2021.12942
|View full text |Cite
|
Sign up to set email alerts
|

Slug promotes p53 and p21 protein degradation by inducing Mdm2 expression in HCT116 colon cancer cells

Abstract: Our previous study revealed that the tumor suppressor/transcription factor p53 directly binds to its transcriptional target, p21, and that the p53/p21 complex binds to zinc finger protein SNAI2 (Slug), a tumor promoter/transcription factor; thereby promoting the degradation of Slug by Mdm2, an E3 ligase. The present study demonstrated that Slug reduced the cellular expression levels of p53 and p21 in HCT116 colon cancer by decreasing their protein stability. In parallel, Slug increased the mRNA and protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The latter can also undergo Mdm2-mediated degradation, but this process is p53-independent. In addition, Slug has been shown to directly activate Mdm2 expression ( Kim J. et al, 2021 ). Importantly, the RING domain of Mdm2 was revealed to be able to interact with RNA.…”
Section: P53-mediated Effects On Emt At the Protein Stability Levelmentioning
confidence: 99%
“…The latter can also undergo Mdm2-mediated degradation, but this process is p53-independent. In addition, Slug has been shown to directly activate Mdm2 expression ( Kim J. et al, 2021 ). Importantly, the RING domain of Mdm2 was revealed to be able to interact with RNA.…”
Section: P53-mediated Effects On Emt At the Protein Stability Levelmentioning
confidence: 99%
“…The molecule increases MDM2 oncogenic activity, and promotes P53 and P21 cellular expression deficiency by degrading them. A study group analyzing its effect in vitro on HCT116 cells showed that a Slug-dependent P53 decrease is an important genetic event that crucially desynchronizes cell cycle phase succession ( 35 ). Moreover, DJ-1 has been found to modulate the TP53/MDM2 signaling pathway by disrupting their interaction and reducing BCL2-, BAX, and CASPASE-3 activity, leading to increased cell proliferation and decreased apoptotic rates ( 36 ).…”
Section: P53/mdm2 Alterations In Colon Adenocarcinomamentioning
confidence: 99%
“…ZNF384 [ 100 ], SNAI2 [ 103 ], and ZEB2 [ 107 ] are upregulated in CRC and enhance MMP2 expression and/or activity, promoting angiogenesis. SNAI2 , which expedites p53/p21 degradation by upregulating MDM2 [ 101 ], is essential for mutant-KRAS cancer cell survival after EMT [ 104 ]. ZNF24 represses VEGF expression [ 109 ] to suppress angiogenesis, while ZKSCAN3 , an inducer of VEGF to promote CRC development and invasion, is implicated in carcinoembryonic antigen (CEA)-producing tumor liver metastasis [ 110 ].…”
Section: Zfps Modulate Crc Cell Proliferation Differentiation Migrati...mentioning
confidence: 99%